2000
DOI: 10.1001/archneur.57.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association of Estrogen Receptor α Gene Polymorphisms and Transcriptional Activity With Alzheimer Disease

Abstract: Background: Long-term cognitive decline in postmenopausal women is associated with aging and Alzheimer disease (AD). Estrogen replacement therapy has been reported to reduce the risk of developing AD. The distribution of estrogen receptors (ERs) in neurons overlaps that of the brain neurons known to develop AD. Estrogen increases the secretion and metabolism of amyloid precursor protein, may help synapse formation, and is reported to protect neurons from toxins. Restriction fragment length polymorphisms (RFLPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 36 publications
4
116
1
3
Order By: Relevance
“…Other case-control studies have found no significant associations [12][13][14], although the small sample sizes in several cases meant a lack of statistical power.…”
Section: Ryan 10mentioning
confidence: 84%
See 3 more Smart Citations
“…Other case-control studies have found no significant associations [12][13][14], although the small sample sizes in several cases meant a lack of statistical power.…”
Section: Ryan 10mentioning
confidence: 84%
“…Previous case-control studies which have directly tested for an ESR1 x ApoE-ε4 interaction however, have failed to find a significant association (p>0.10) [15,16,21,43]. Notably however, most of these null findings have accompanied studies which have also failed to find an independent association between rs2234693 and AD [14,19,21,43]. Findings from animal studies do suggest that estrogen and ApoE can interact in the brain.…”
Section: Ryan 12mentioning
confidence: 97%
See 2 more Smart Citations
“…However it remains unknown whether and by which mechanism the two studied polymorphisms may affect ESR expression. In vitro studies have demonstrated that enhancer activity differs, although not significantly, among ESR1 haplotypes, the highest being associated with ESR1 xp haplotype and ESR1*x allele [22] . This difference suggested that the expression of ESR1 could be regulated depending on the ESR1 genotype.…”
Section: Discussionmentioning
confidence: 98%